Legal Protection for Creditors in Commercial Property Disputes: A Case Study of the Court Decision - Malau, Hotmaulina; Seroja, Triana Dewi; Sudirman, Lu (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
Commercial property disputes between creditors and debtors are on the rise, particularly in industrial cities such as Batam. Creditors frequently encounter significant challenges, including the risk of default, third-party claims, and obstacles in executing collateral—largely driven by regulatory uncertainty and weak law enforcement. This study aims to examine the legal protection available to creditors in commercial property disputes, with a focus on District Court Decision No. 158/Pdt.G/Plw/Gs/2022/PN Btm. Utilizing a normative juridical approach, the research highlights a clear disconnect between existing legal provisions and their practical implementation in safeguarding creditor rights. Key barriers faced by creditors include prolonged execution processes, lack of transparency in credit agreements, and insufficient financial literacy among debtors. [Semakin meningkat, terutama di kota industri seperti Batam. Kreditur sering menghadapi risiko wanprestasi, klaim pihak ketiga, dan hambatan eksekusi jaminan yang disebabkan oleh ketidakpastian regulasi serta lemahnya penegakan hukum. Penelitian ini bertujuan untuk menganalisis perlindungan hukum bagi kreditur dalam sengketa properti komersial berdasarkan Putusan Pengadilan Negeri Batam No. 158/Pdt.G/Plw/Gs/2022/PN Btm. Metode penelitian yang digunakan adalah pendekatan yuridis normatif. Hasil penelitian menunjukkan bahwa terdapat kesenjangan antara ketentuan hukum yang ada dengan implementasi perlindungan kreditur di lapangan. Hambatan utama yang dihadapi kreditur meliputi proses eksekusi yang berlarut-larut, kurangnya transparansi dalam perjanjian kredit, serta minimnya edukasi bagi debitur].